The investigation of indoor air temperature effects for different types of window dimensions using CFD simulation / Nor Azirah Mohd Fohim ... [et al.] - Mohd Fohimi, Nor Azirah; Mohd Nasir, Siti Shareeda; Hussin, Norasikin; Mahmod@Wahab, Rohidatun; Sulong, Nurulsaidatulsyida (Smart Manufacturing Research Institute (SMRI), 2023)
Windows plays an important role in heat transfer and natural ventilation in buildings. In the field of building design, the challenge is to provide a thermally comfortable indoor environment that requires the least energy consumption to maintain. One of the energy reduction alternatives that can be incorporated into modern building design is the installation of efficient windows. The windows should allow thermally acceptable indoor air quality and have a pleasant design while being energy efficient. Good thermal conditions in school buildings, especially learning spaces, promote the educational process. Unfulfilling comfort levels can reduce the lecturers' and students' physical and intellectual performance. One of the variables that affect the thermal comfort condition is indoor air temperature. The purpose of this study is to investigate the effect of different types of window dimensions on indoor air temperature by using Computational Fluid Dynamics (CFD) simulation. The selected classroom at Universiti Teknologi MARA (UiTM) Permatang Pauh, Pulau Pinang will be used as a case study. The field measurement result can be used to validate the simulation result. The simulation result will be compared to standard regulations set by the American Society of Heating, Refrigeration, and Air Conditioning Engineers (ASHRAE) Standard 55-2017. Three different types of window dimensions have been chosen in this study which are double, triple, and quadruple-glazed windows. The validation result shows the percentage difference in indoor air temperature between the experimental and simulation is 1.04 %. The result found double and triple-glazed windows show the value of temperature under the range set by ASHRAE Standard 55-2017. The selection of triple-glazed windows is more suitable because the brightness of the classroom meets the criteria for the absence of direct solar radiation. In conclusion, window dimension is a parameter that affects heat transfer and indoor air temperature of the classroom.